Penggunaan model pembelajaran discovery learning untuk meningkatkan kemampuan penalaran matematis siswa SMP - Septianingrum, Berliana Dwina; Zanthy, Luvy Sylviana; Senjayawati, Eka (IKIP Siliwangi, 2025)
The aim of the research is to find out whether there is an increase in students' mathematical reasoning abilities with the discovery learning learning model compared to ordinary learning. The method used was quasi-experimental with a non-equivalent pretest-posttest design. The population in this study were class VIII students at SMP PGRI 1 Cimahi. The sample in this study was 30 students from class VIII-C and class VIII-D for each class. Class VIII-C is used as an experimental class and class VIII-D is used as a control class. The data collection technique in this research was through a written test consisting of six descriptive questions. The data obtained will be analyzed and processed with the help of IBM SPSS version 26 for Windows software. Based on the research results, H_0 was rejected and H_1 was accepted, meaning that there was an increase in the mathematical reasoning abilities of students whose learning used regular learning. Thus it can be concluded that there is an increase in mathematical reasoning abilities in the experimental class which uses the Discovery Learning Learning Model.